Piotr Lasek and Wojciech Wółkowski. Conrada Steinbrechta pruskie zamki biskupie i kapitulne [Conrad Steinbrecht’s Prussian bishops’ and cathedral chapters’ castles].: Warszawa: Instytut Sztuki Polskiej Akademii Nauk, 2025. 270 pp., 71 illus. ISBN 978-83-66519-99-2. - Kwiatkowski, Krzysztof (Ordines Militares Colloquia Torunensia Historica. Yearbook for the Study of the Military Orders, 2025)